2018-2019 Florida Citrus Production Guide: Citrus Canker - Megan M. Dewdney; Evan G. Johnson; James H. Graham (EDIS)
Citrus canker, caused by the bacterium Xanthomonas citri subsp. citri, is a leaf, fruit, and stem blemishing disease that affects most citrus. This 6-page fact sheet is part of the 2018-2019 Florida Citrus Production Guide. Written by M. M. Dewdney, E. G. Johnson and J. H. Graham, and published by the Plant Pathology Department, February 2019.